Incidence, species and antimicrobial resistance of naturally occurring Campylobacter isolates from quail carcasses sampled in a commercial processing facility. Issue 2 (15th January 2018) - Cox, N. A.; Cosby, D. E.; Thippareddi, H.; Ritz, C. W.; Berrang, M. E.; Jackson, J. S.; Mize, S. C.; Kumar, S.; Howard, A. K.; Rincon, A. M.; Ukidwe, M. S.; Landrum, M. A.; et al.
Abstract: There is limited information about Campylobacter in commercially processed quail ( Coturnix coturnix ). The objective of this study was to determine the occurrence of Campylobacter on carcasses in a commercial quail processing plant. Carcasses were collected prior to chilling and/or the application of any antimicrobials, transported to the laboratory, and individually bagged. Following the standard protocol for recovering Campylobacter, three typical colonies were selected, confirmed as Campylobacter and tested for antimicrobial susceptibility. Nine replicates were conducted. Of the 85 carcasses obtained (n = 5 for first visit, n = 10 for 8 subsequent visits), 28 (32.9%) carcasses were found to be positive for Campylobacter . On four visits, no Campylobacter was found; on two visits, all samples were positive; and 1/5, 1/10, and 6/10 samples were positive for the remaining visits. Of the 28 isolates recovered, 18 (64%) were C. jejuni and 10 (36%) were C. coli . Tetracycline resistance was detected in all 28 isolates. Future work in the breeder flocks, hatchery, and grow‐out houses is planned to further understand Campylobacter ecology in quail production and processing which could also be useful to the broiler industry. Practical applications: Very little published information exists for the presence of Campylobacter spp. on processed quail. Most of the studies involve cloacal swabs and ceca from samples obtained from hunters. This study involves sampling processed quail carcasses from a large commercial integrated company and also determined the species and antibiotic resistance profile of the Campylobacter isolates. There is considerable debate concerning the ecology of Campylobacter on poultry and perhaps our data can be used by the broiler industry to develop a better understanding of the ecology and to assist in the application of effective intervention strategies. Presently, there is slightly under 100, 000 million commercially processed and domestically grown quails in the United States each year, most of which is marketed in Europe as a frozen product. So the presence of an important foodborne pathogen on this food is significant information.